Seroprevalence of hepatitis B infections among blood donors in Bijapur district Karnataka - Retrospective study - Patil, Prakash Murigeppa; Patil, Vijaylaxmi. S.; Yelikar, Balasaheb R.; Bhalodia, Mihir J.; Gudadinni, Muttappa R.; Shannawaz, Mohd (Asian Journal of Medical Sciences, 2014)
Objectives: To determine the seroprevalence of HBsAg in the prevalence of HBsAg positivity among male and female blood donors. Materials and Methods: A retrospective study was conducted in blood bank. Voluntary and replacement blood donors including male and female donors over a period of two years six month to assess the prevalence of hepatitis B virus infection. ELISA method and alternatively Hepacard kit were used for screening the donors. Results: A retrospective study was carried on 7,018 blood donors out of which males were 5,936 and 1,082 were females. The prevalence of HBsAg sero positivity in 2011 July to December in male donors were 2.8%; in female donors 0.0%; 2012 January to December in male donors were 2.9% and female donors were 0.3%; 2013 January to December in male donors were 1.8% and Female donors were 0.0% . Overall prevalence was estimated to be 7.8%. Conclusion: Hepatitis B infection remains a significant public health problem in India and its seroprevalence was more as compared to other transfusion transmitted infections, especially in younger age group. The increasing prevalence of HBsAg can be reduced by more sensitive screening assays. DOI: http://dx.doi.org/10.3126/ajms.v6i3.10862 Asian Journal of Medical Sciences Vol.6(3) 2015 12-15